Parainfluenza virus 5 (PIV5) amplifying virus-like particles expressing respiratory syncytial virus (RSV) antigens protect mice against RSV infection. Issue 22 (16th May 2019) - Huertas-Díaz, María Cristina; Phan, Shannon; Elson, Andrew; Nuñez, Ivette; Wei, Huiling; Sakamoto, Kaori; He, Biao
Abstract: Respiratory syncytial virus (RSV) is the leading cause of bronchiolitis and pneumonia in children under one year of age. In addition to causing severe respiratory diseases in children, it is also a major cause of morbidity and mortality among the elderly and immunocompromised individuals. RSV is the most common cause of lower respiratory tract infections, yet there are currently no licensed vaccines. A parainfluenza virus 5 (PIV5)-based amplifying virus-like particle (AVLP), which enables the use of PIV5 RNA transcription/replication machinery to express gene of interest, has recently been developed. We evaluated the PIV5-based AVLP system as a vaccine platform for RSV by incorporating the fusion protein (F) gene and the transcription factor protein (M2-1) gene of RSV into the PIV5-AVLP backbone (AVLP-F and AVLP-M2-1, respectively). Mice immunized with a single dose of the AVLP-F or AVLP-M2-1 developed RSV-F or RSV-M2-1-specific immune responses, respectively. Both vaccine candidates elicited antigen-specific cell-mediated responses at levels comparable to or higher than an RSV infection. Most importantly, each vaccine was able to induce protection against RSV A2 challenge in the mouse model. These results indicate the potential of the PIV5-based AVLP system as a platform for vaccines against RSV infection.